2021
DOI: 10.3171/2019.10.jns191932
|View full text |Cite
|
Sign up to set email alerts
|

Critical area for memory decline after mesial temporal resection in epilepsy patients

Abstract: OBJECTIVEMesial temporal lobe epilepsy (MTLE) surgery is associated with a risk of memory decline after surgery, but the effect of the extent and locus of temporal resection on postoperative memory function are controversial. The authors’ aim in this study was to confirm if selective resection is effective in preserving memory function and identify critical areas for specific memory decline after temporal resection.METHODS Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 41 publications
(44 reference statements)
0
15
0
Order By: Relevance
“…However, there was no significant difference between FPD and NMC or between IPD and HC in this region. The superior temporal area is a region known to subserve memory, which is also commonly affected in PD 63‐68 . Volume loss in the superior temporal region has been reported to be associated with cognitive decline in PD 64,69‐71 .…”
Section: Discussionmentioning
confidence: 99%
“…However, there was no significant difference between FPD and NMC or between IPD and HC in this region. The superior temporal area is a region known to subserve memory, which is also commonly affected in PD 63‐68 . Volume loss in the superior temporal region has been reported to be associated with cognitive decline in PD 64,69‐71 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the improvement of postoperative visual memory and IQ following TP-AH is evidence that the resection of the temporal pole is less impactful on neurocognitive performance than a combined impact of other factors such as preoperative functional reserve, age at seizure onset, resection of critical temporal areas, the magnitude of epilepsy network disconnection, and seizure control. 7,42,43 A major concern related to epilepsy surgical treatment is whether reducing the resection of nonpathological tissue may affect seizure control and postoperative side effects simultaneously. In a cohort of 95 patients with HS, McIntosh et al reported an Engel I rate of 54.2% 5 years after standard ATL.…”
Section: Discussionmentioning
confidence: 99%
“…The contralateral hemifield was evaluated, and the result was classified as (1) normal perimetry or visual field not attributable to surgery, (2) quadrant VFD F I G U R E 1 Drawings illustrating the transsylvian amygdalohippocampectomy at the right hemisphere. After the Sylvian fissure is dissected, anatomical landmarks are observed: frontal lobe (1), temporal pole (2), internal carotid artery (3), M1 segment of the middle cerebral artery (4), oculomotor nerve (5), limen insula (6), and uncus (7). The topography of the amygdala and the hippocampus (A) correspond to the regions surrounded by small dots and highlighted in yellow and blue, respectively.…”
Section: Perimetrymentioning
confidence: 99%
See 2 more Smart Citations